A Recently Evolved Transcriptional Network Controls Biofilm Development in Candida albicans - Nobile, Clarissa J.; Fox, Emily P.; Nett, Jeniel E.; Sorrells, Trevor R.; Mitrovich, Quinn M.; Hernday, Aaron D.; Tuch, Brian B.; Andes, David R.; Johnson, Alexander D. (Cell, 2012)
A biofilm is an organized, resilient group of microbes in which individual cells acquire properties, such as drug resistance, that are distinct from those observed in suspension cultures. Here, we describe and analyze the transcriptional network controlling biofilm formation in the pathogenic yeast Candida albicans, whose biofilms are a major source of medical device-associated infections. We have combined genetic screens, genome-wide approaches, and two in vivo animal models to describe a master circuit controlling biofilm formation, composed of six transcription regulators that form a tightly woven network with ∼1,000 target genes. Evolutionary analysis indicates that the biofilm network has rapidly evolved: genes in the biofilm circuit are significantly weighted toward genes that arose relatively recently with ancient genes being underrepresented. This circuit provides a framework for understanding many aspects of biofilm formation by C. albicans in a mammalian host. It also provides insights into how complex cell behaviors can arise from the evolution of transcription circuits. [Display omitted] ► Candida biofilms are controlled by a network of six master transcription regulators ► The biofilm network is highly interconnected and contains > 1,000 target genes ► Computational analysis indicates that the biofilm network has rapidly evolved ► The network interconnectedness provides clues as to how complex circuits evolve Biofilms of the pathogenic fungus C. albicans coat medical devices and contribute to drug-resistant infections. Revealing the transcriptional circuit responsible for biofilm formation provides insight into how complex cell behaviors arise from the evolution of regulatory circuits.